Extimating Life Cycle labor Supply Tax Effects - Ziliak, James P.; Kniesner, Thomas J. (Journal of Political Economy, 1999)
We present an econometrically tractable life cycle labor supply model for panel data including intertemporally progressive taxes on uncertai wage and nonwge incomes. Our two‐stage fixedeffects generalized method‐of‐moments approach first extimates intretemporal and then intertemporal preferences. Specification testing domonstrates the value of incorporating joint progressive taxation of labor and nonlabor incomes, Results for prime‐age men emphasize the roles played by hourly wage endogeneity, worker‐specific effects, the measure of the rate of pay, and intemporal budget constaint, nonseparability, Simulations indicate that recent tax reform, while not self‐financing, stimulated made labor supplied by about 3 percent and reduced deadweight loss about 16 percent.